Critical Analysis of Foundational Healthcare Practices in Diverse Settings - Hefshan, Saleh Dafer Taleb; Al Abbas, Rasheed Hadi Mohsen; Al Abbas, Saleh Hadi Ali; Al Alabbas, Ibrahim Hadi Ali; Al Rashah, Abdul Mohsen Yahya Mohsen; Alrashah, Ahmed Yahya Mohsen; Alsagoor, Mohsen Mubark Ali; al Abbas, Mahdi Saleh shettah; alshhai, Ali mohsen saeed; Alshetah, AlHassan Rshed Mahde (Journal of Ecohumanism, 2024)
Healthcare delivery systems vary depending on the economies, cultures, and infrastructures of the regions of the globe. Healthcare practices across various contexts should be used as building blocks of basic healthcare systems and concepts to design better healthcare systems. This paper critically evaluates essential healthcare practices in various contexts because it considers HICs, LMICs, and rural or remote regions. Based on a combination of case studies, review articles and evidence-based literature, this analysis assesses fundamental tenets of healthcare delivery: accessibility, quality, and sustainability. The paper focuses on modern and emerging healthcare modalities and discusses issues that are relevant today, including disparities and inequalities, shortage of resources, and human capital. This evokes a discussion of technology, public health policies, and global health programs before providing the authors’ suggestions for advancing health care globally.